Non-Targeted Metabolomics of White Rhinoceros Colostrum and Its Changes During Early Lactation by 1H Nuclear Magnetic Resonance Spectroscopy - Gernot Osthoff; Petronella Nieuwoudt (Metabolites)
Background/Objectives: Dynamic changes in components from colostrum to mature milk occur in any mammal. However, the time it takes to reach the mature milk stage differs between taxa and species, as do the final concentrations of all the components. The white rhinoceros belongs to the family Perissodactyla, of which the milk and milk metabolome of the domesticated Equidae have been studied to some detail. Metabolomic information on the colostrum and milk of the Rhinocerotidae is lacking. Methods: Colostrum and milk were obtained from seven white rhinoceroses. Of note is that it was their first parturition and all followed the same diet, two factors known to affect colostrum composition and its changes during early lactation in domesticated mammals. Milk serum was prepared by the ultrafiltration of the milk samples. Untargeted 1N NMR spectra were processed with Topspin 3.2, calibration was carried out according to the alanine signal and the identification of signals was carried out with Chenomx and assignments in the literature. Statistical analysis of the data was carried out using MetaboAnalyst 6.0. Results: The changes in the metabolites were followed during the first 7 days of lactation as well as on day 20. The amounts of amino acids and their derivatives, organic acids and lipid metabolites decreased over lactation, while carbohydrates and their derivatives increased. The colostrum phase ended on day 2, while the transition to mature milk seemed to be complete by day 7. From day 3 to 7, galactose metabolism and tyrosine metabolism were uprated. Of interest is the presence of the oligosaccharide 3′-sialyllactose on days 3 and 4 of lactation. Conclusions: Mainly the content of carbohydrates increased over lactation, specifically lactose. The 3′-sialyllactose content peaked on days 3 and 4 of lactation. The colostrum phase ended on day 2. The mature milk stage was reached by day 7. The galactose metabolism and tyrosine metabolism were uprated after day 3 of lactation.